Blood Pressure Variability Is Associated with Hearing and Hearing Loss: A Population-Based Study in Males - Minghui Bao; Yongjian Song; Jun Cai; Shouling Wu; Xinchun Yang (International Journal of Hypertension)
Blood pressure (BP) has been well documented to be associated with hearing loss previously. However, the role of blood pressure variability (BPV, representing BP fluctuation over a time period) on hearing remains unknown. We aimed to evaluate the relationship between BPV and hearing in Chinese population. We included 8646 male subjects from a population-based study (the Kailuan study). BP was measured every two years at routine physical examinations from 2006 to 2015. Based on five annual BP measurements, BPV was estimated by standard deviation of BP (SD), coefficient of the variation of BP (CV), and variation independent of mean of BP (VIM). Hearing was estimated by pure-tone average threshold (PTA) at low, intermediate, and high frequencies in the year of 2014. Regression models were used to evaluate the relationship between BPV and hearing. The results showed that PTAs and percentages of hearing loss at low, intermediate, and high frequencies grew gradually with increasing systolic SD (SSD) (p<0.05). After adjusting for multiple covariates, multivariate regression analyses demonstrated that variations of SBP (SSD, SCV, and VIMSBP) were all positively correlated with PTA at intermediate and high frequencies (p<0.05). Each SD increase in SSD, SCV, and VIMSBP was also positively associated with hearing loss at intermediate and high frequencies. No significant correlation was observed between variations of DBP and hearing. These findings suggest that increase in long-term BPV is associated with hearing and hearing loss. Trial registration number: Kailuan study (ChiCTRTNC-11001489).